2012
DOI: 10.5923/j.jce.20120206.07
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Lime and Grand Granulated Blast Furnace Slag (GGBFS) Mixture for Stabilisation of Desert Silty Sands

Abstract: This study describes experimental results achieved on the use of Grand Granulated Blast Furnace Slag (GGBFS) and Lime in stabilising desert silty sand for possible use in geotechnical engineering applications, especially for roadways and railways constructions. The GGBFS and lime were added in percentages of 5, 10 and 15% and 1, 3, and 5% respectively, by dry weight of sand. Different laboratory tests such as mechanical aggregation test, hydrometer analysis, liquid-plastic limit , p H value test, compaction, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Amer et al [7] showed that with the addition of 6% lime, both the swell percent and swell pressure reduced to zero. Rabbani et al [15] evaluated the use of Grand Granulated Blast Furnace Slag (GGBFS) and lime in stabilizing desert silty sand for possible use in geotechnical engineering applications, especially for roadways and railways constructions. Results indicated that the swelling behavior of mixtures was decreased effectively.…”
mentioning
confidence: 99%
“…Amer et al [7] showed that with the addition of 6% lime, both the swell percent and swell pressure reduced to zero. Rabbani et al [15] evaluated the use of Grand Granulated Blast Furnace Slag (GGBFS) and lime in stabilizing desert silty sand for possible use in geotechnical engineering applications, especially for roadways and railways constructions. Results indicated that the swelling behavior of mixtures was decreased effectively.…”
mentioning
confidence: 99%
“…It should be noted that the role of IHL in this study is to be an activator for chemical reaction rather than being the main stabiliser. Previous investigations found that the 5:1 BFS:lime ratio is proper to activate BFS (Wild and Tasong, 1999; Rabbani et al., 2012), however, the 4:1 ratio was preferred in this study to assure all ACBFS will be activated and to minimise the ACBFS content.…”
Section: Methodsmentioning
confidence: 87%
“…As shown in Table 6, adding the ACBFS-IHL slurry reduced both the initial saturated and dry unit weight of the mixtures. Previous research demonstrated that adding BFS powder to soil should increase the mixture's unit weight by filling the voids between soil particles (Akinmusuru, 1991; Wild et al., 1996; Rabbani et al., 2012). However, for the given additive contents in this research, the effect of lime and water has been the dominant factor in controlling the unit weight of the mixture.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrated lime has a purity level of Ca(OH) 2 , a minimum of 90%, and the particle size analysis shows that 90% of the grain size is less than 90 micron. When lime is added to silicon and aluminum oxides (within soils or added volcanic ash) with the presence of water, pozzolanic reactions occur and lead to forming calcium silicate hydrate (C-S-H) and calcium aluminate hydrate (C-A-H) gels that, after crystallization, will substantially contribute to connecting the soil particles to a relatively strong structure [ 15 ].…”
Section: Materials Usedmentioning
confidence: 99%
“…The results showed a substantial increase in the UCS of the stabilized sand by adding 3% lime and 15% bentonite. Rabbani et al [ 15 ] investigated the influence of ground granulated blast furnace slag (GGBFS) and lime on the geotechnical properties of dune sands of Iran for possible usage in roadways and railways projects. The results showed significant improvement in the CBR and UCS of the treated sand.…”
Section: Introductionmentioning
confidence: 99%